2015
DOI: 10.1111/srt.12274
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in scalp hair growth rates are maintained but reduced in pattern hair loss compared to controls

Abstract: In pattern hair loss, LHGR significantly contributes to the apparent decrease in hair volume in affected areas. In early onset, LHRG might have a prognostic value in females but not in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Yet, if is true then, in general, all absorbed dietary protein is only utilized for EE ; and thus, over time, total body protein persistently decreases because the EE -independent protein loss is not being compensated by dietary intake. EE -independent protein loss occurs in feces (e.g., excretion of mucin, an indigestible protein secreted by the intestinal mucosa [ 27 ]), in sweat (e.g., amino acids may be excreted during physical exertion [ 28 ]), in urine (e.g., urinary excretion of glycine in creatinine [ 29 ] and C-peptide [ 30 ], a 31 amino acid polypeptide generated from insulin secretion) and during renewal of skin, hair and nails (e.g., shedding of dead cells filled with keratin [ 31 , 32 , 33 ]). As a consequence, we run into a contradiction since body weight is simultaneously stable (true absorbed-oxidation identities imply mass balance) and decreasing (body protein is continuously diminishing).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Yet, if is true then, in general, all absorbed dietary protein is only utilized for EE ; and thus, over time, total body protein persistently decreases because the EE -independent protein loss is not being compensated by dietary intake. EE -independent protein loss occurs in feces (e.g., excretion of mucin, an indigestible protein secreted by the intestinal mucosa [ 27 ]), in sweat (e.g., amino acids may be excreted during physical exertion [ 28 ]), in urine (e.g., urinary excretion of glycine in creatinine [ 29 ] and C-peptide [ 30 ], a 31 amino acid polypeptide generated from insulin secretion) and during renewal of skin, hair and nails (e.g., shedding of dead cells filled with keratin [ 31 , 32 , 33 ]). As a consequence, we run into a contradiction since body weight is simultaneously stable (true absorbed-oxidation identities imply mass balance) and decreasing (body protein is continuously diminishing).…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Gender, hair diameter and health status are significant factors influencing hair growth rates and there is a slightly faster mean growth rate in females as compared to males 24 . In the present study, gender difference in the speed of hair growth was also found in C57BL/6Mlac mice (with a slightly faster in females) as evaluated in the control groups either by the initial hair growth (the first hair growth being visualized) as well as complete hair growth (the whole depilated area being occupied with hair) in Table 1, or percent area of hair growth in Table 2.…”
Section: Hair Growth Ratementioning
confidence: 99%
“…The earliest measurements in affected follicles involve a shortening of the anagen phase, an increase in telogen (shed) hairs and, in particular, those telogen club hairs ≤30 mm in length, a reduced rate of hair growth, followed by a reduction in hair diameter. 19 , 20 , 21 From the clinical point of view, a substantial amount of individual hair follicle regression is required before noticeable hair loss is perceived by clinicians (>15% 19 ).…”
Section: Background—tracking Hair Follicle Miniaturisationmentioning
confidence: 99%